The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e04281
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuroticism and extraversion in the emotional health of people with cancer

Abstract: The impact that cancer disease can have on individuals varies depending, among other things, on their personal characteristics, so it is important to explore aspects such as the personality traits in relation to mental health in people with cancer. The aim of this study was to analyse the relationship between neuroticism, extraversion and mental health in people with cancer. Besides, this study also explored differences in mental health when combining extraversion and neuroticism levels. One hundred and sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Individuals who are highly neurotic and introverted (i.e., reserved, withdrawn, inhibited) might present less adaptive coping strategies in reaction to potentially stressful events, and thereby experience more psychological distress. Furthermore, the present result is in line with the findings of Macía et al (2020), who showed that low levels of neuroticism and high levels of extraversion related to positive health outcomes, and seemed to comprise protective factors with respect to mental health in cancer patients. Finally, the result is aligned with that of Mulsow et al (2002), who found that high levels of extraversion, agreeableness, and emotional stability (i.e., low levels of neuroticism) were associated with lower levels of parenting stress in mothers of newborns, thereby decreasing the likelihood that these mothers would experience chronic distress after 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals who are highly neurotic and introverted (i.e., reserved, withdrawn, inhibited) might present less adaptive coping strategies in reaction to potentially stressful events, and thereby experience more psychological distress. Furthermore, the present result is in line with the findings of Macía et al (2020), who showed that low levels of neuroticism and high levels of extraversion related to positive health outcomes, and seemed to comprise protective factors with respect to mental health in cancer patients. Finally, the result is aligned with that of Mulsow et al (2002), who found that high levels of extraversion, agreeableness, and emotional stability (i.e., low levels of neuroticism) were associated with lower levels of parenting stress in mothers of newborns, thereby decreasing the likelihood that these mothers would experience chronic distress after 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies reveal that neuroticism is positively associated with various psychological problems, which is consistent with our study (36)(37)(38)(39). At the same time, higher levels of extraversion are also found to be related to positive health outcomes (40).…”
Section: Discussionsupporting
confidence: 92%
“…In the context of caregiving, the stress model underlines the importance of the perceived lack of control and the psychological stress involved in the situation of caring compared with the objective amount of expected burden as a result of the degree of mental impairment or dependency of the elderly patient [ 14 ]. Some authors suggested that the time spent providing care, the caregiver’s age, their lack of social support, the cognitive impairment of the elderly, and the caregiver’s neuroticism are important factors [ 15 , 16 ]. Previous studies also found differences in the amount of perceived burden in caregivers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%